Green Pavement using Recycled Polyethylene Terephthalate (PET) as Partial Fine Aggregate Replacement in Modified Asphalt - Wan Mohd Nazmi, Wan Abdul Rahman; Achmad Fauzi, Abdul Wahab (Elsevier Ltd, 2013)
Most plastics collected for recycling from the household waste stream are plastic bottles. The majority of bottles are made from Polyethylene Terephthalate (PET) estimated that the ratio is 55-60%. The objective of this research is to determine optimum quality and the effect usage of recycled PET as partial fine aggregate replacement in modified asphalt mixture by determining the permanent deformation and stiffness behaviour. The modified asphalt mixtures were produced from content concentrate of recycled PET pallet range between 5 and 25% of the weight of asphalt mixture with sieve size from 2.36 mm to 1.18 mm and 5% weight of bitumen content as follow hot mix asphalt wearing course 14 (ACW14) in Standard Specification of Road Work in Malaysia. The samples were subjected to Repeated Load Axial Test (RLAT) loading for 1800 cycles and axial load applied 100 kN at to determine permanent deformation of modified asphalt mixture. The Indirect Tensile Stiffness Modulus Test (ITSM) was used to evaluate stiffness modified asphalt sample at 25 °C. The result obtained from the lab testing reveals the maximum permanent deformation of modified asphalt mixture reach at 20% replacement with recycled PET. However the stiffness of PET modified asphalt mixtures tend to decrease compare to unmodified asphalt mixture. The finding indicates that PET has ability to improve permanent deformation properties of asphalt mixture. In the environmental and economical aspects, PET modified asphalt mixture is found suitable to be used for road pavements.